2007
DOI: 10.1002/art.22833
|View full text |Cite
|
Sign up to set email alerts
|

Pre–B cell colony‐enhancing factor/visfatin, a new marker of inflammation in rheumatoid arthritis with proinflammatory and matrix‐degrading activities

Abstract: Objective. To study possible mechanisms that mediate induction of the recently described adipocytokine pre-B cell colony-enhancing factor (PBEF) in joints of patients with rheumatoid arthritis (RA), and to analyze whether levels of PBEF correlate with disease severity and whether PBEF itself has the potential to act as a proinflammatory and destructive mediator in RA.Methods. RA synovial fibroblasts (RASFs) and monocytes were stimulated with Toll-like receptor (TLR) ligands, cytokines, and recombinant human PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
224
0
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 238 publications
(252 citation statements)
references
References 34 publications
(47 reference statements)
16
224
0
12
Order By: Relevance
“…PBEF is detectable in serum and synovial fluid (1,6), and the levels of PBEF have been found to be increased in patients with rheumatoid arthritis, in whom it is clinically correlated with the Disease Activity Score in 28 joints and elevated C-reactive protein level (1,2,6). Other groups have detected PBEF in a variety of bodily fluids (35,(38)(39)(40)(41), and the levels appear to be correlated with inflammation (35,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PBEF is detectable in serum and synovial fluid (1,6), and the levels of PBEF have been found to be increased in patients with rheumatoid arthritis, in whom it is clinically correlated with the Disease Activity Score in 28 joints and elevated C-reactive protein level (1,2,6). Other groups have detected PBEF in a variety of bodily fluids (35,(38)(39)(40)(41), and the levels appear to be correlated with inflammation (35,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that PBEF interacts with the insulin receptor (8-10); however, this notion remains controversial (11,12), and it may be that PBEF signals through an alternative signaling route. It is also unlikely that this signaling effect is attributable to the endotoxin that may be present in PBEF preparations, since coincubation with polymixin B shows no abrogation of PBEF signaling (6,10,13).In vitro activation of signaling pathways by PBEF has been shown to regulate the expression of metalloproteinases, chemokines, and cytokines (6,7,(9)(10)(11)(12), but the in vivo contribution of this mediator of arthritis progression remains unclear. The recently developed small molecule inhibitor APO866 has been shown to act as a competitive inhibitor of PBEF/NAMPT activity by inhibiting binding of its natural substrate, nicotinamide (14,15).…”
mentioning
confidence: 99%
See 3 more Smart Citations